Assessing the risk of multiple sclerosis disease-modifying therapies. (3rd July 2019) - Ayrignac, Xavier; Bilodeau, Philippe-Antoine; Prat, Alexandre; Girard, Marc; Labauge, Pierre; Le Lorier, Jacques; Larochelle, Catherine; Duquette, Pierre
ABSTRACT: Introduction : The number of immunomodulatory options approved for multiple sclerosis has increased over the past years, resulting in a better control of the disease. Depending on disease activity, neurologists can now propose treatments with different levels of efficacy, from injectable and oral treatments with modest efficacy, to highly active immunosuppressants. Nevertheless, this gain in efficacy has come with an increase in the global burden of treatment-related adverse events. Areas covered : The authors have reviewed extensively the existing literature to gain insight into the adverse events associated with disease modifying therapies, so as to help neurologists choose the right treatment for their patients. The authors classified and summarized the adverse events based on frequency, severity and relevance. Expert opinion : As the number and diversity of adverse events is expected to increase, careful surveillance of patients under treatment will be even more important. The characteristics of the MS population, i.e. mainly young women of childbearing age, who will remain treated for decades, and the need for serial administration of distinct treatments with different mechanisms of action highlights the importance of a comprehensive risk-benefit assessment.